Characterisation of Plasmodium knowlesi from monkey and human samples in Kapit division, Sarawak - Siti Khatijah, Binti Zakaria. (Universiti Malaysia Sarawak (UNIMAS), 2011)
Plasmodium knowlesi is a malaria parasite naturally found in long-tailed and pig-tailed macaques. Recent studies in the Kapit division of Sarawak showed that there was a large focus of naturally acquired P. knowlesi infections in humans. Studies on macaques in the Kapit Division have shown that they harbour knowlesi malaria parasites and other typse of monkey ,alarias. It is important to study the mode of transmission of P. knowlesi in order to establish whether human infections of P.knowlesi are zoonotic or acquired from other humans so that preventive measures against the disease can be taken.